Macroeconomic Determinants, Efficiency, and Policy Drivers of Welfare Performance in Islamic Fintech: The Mediating Role of Systematic Risk in Indonesia - Adi Suroso; Indriana Kristiawati; Naurah Aurelia Mahjudin (PT. Mawadaku Sukses Solusindo, 2025)
This study explores the influence of macroeconomic fundamentals, cost efficiency, and corporate policy decisions on the welfare performance of Islamic financial technology (FinTech) firms in Indonesia—an emerging economy. The analysis adopts a sequential approach, incorporating systematic risk and firm performance as mediating variables. Specifically, the study examines the indirect effect of macroeconomic variables on firm performance and firm value through systematic risk, while also assessing the mediating role of firm performance in transmitting the effects of macroeconomic factors and corporate decisions. Grounded in agency theory and capital structure theory, the study employs panel data from listed Islamic FinTech institutions in Indonesia, with active trading records on the Indonesia Stock Exchange during the 2017–2019 period. The results reveal that macroeconomic indicators—namely inflation, interest rates, exchange rates, and GDP growth—significantly affect systematic risk, which in turn influences firm performance, subsequently impacting firm value. Additionally, corporate policies such as managerial incentives and financial leverage exhibit strong direct effects on firm performance and, indirectly, on firm value. However, capital expenditures appear to have no statistically significant effect on either outcome. Notably, firm performance functions as an essential mediating variable in the relationship between exchange rates, systematic risk, and policy factors—specifically managerial incentives—and the welfare performance of Islamic FinTech firms.